The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1606/1044-3894.108
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Help Lines among Sociopolitical Minorities: A View from Both Sides of the Line

Abstract: The purpose of this study was to evaluate the effectiveness of a 3-year help line project as an alternative modality of help among the Arab population living in Israel. Specifically, the authors examined the perception and experience of help among both users and service providers. The research sample consisted of 131 callers and 15 volunteers. Questionnaire items included the reason for and timing of the call, the degree of help received, and the extent of improvement in the problem. Findings show a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…5,15,40 Various other factors may also account for these discrepancies: differences in help-seeking characteristics 41 ; the stigma attached to seeking help from sources outside the family support network; the level of knowledge about eating disorders and eating disorder treatment facilities; and the sociocultural changes that the Israeli-Arab population is undergoing due to the Western-oriented influence of modern life in Israel. 41 The low incidence of eating disorders may also represent an interesting cultural phenomenon characteristic of other minority groups in terms of disclosure patterns for eating disorders. In line with the research demonstrating the influence of ethnicity on help-seeking characteristics, two recent studies showed low rates of treatment seeking in an ethnically diverse sample of individuals with eating disorders.…”
Section: Resultsmentioning
confidence: 99%
“…5,15,40 Various other factors may also account for these discrepancies: differences in help-seeking characteristics 41 ; the stigma attached to seeking help from sources outside the family support network; the level of knowledge about eating disorders and eating disorder treatment facilities; and the sociocultural changes that the Israeli-Arab population is undergoing due to the Western-oriented influence of modern life in Israel. 41 The low incidence of eating disorders may also represent an interesting cultural phenomenon characteristic of other minority groups in terms of disclosure patterns for eating disorders. In line with the research demonstrating the influence of ethnicity on help-seeking characteristics, two recent studies showed low rates of treatment seeking in an ethnically diverse sample of individuals with eating disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The same tendency was also observed when comparing religious affiliation (Muslim vs. Christian) by gender, as no significant differences were revealed. These findings can be partially understood within the context of the exposure of Israeli-Arabs to the predominantly western culture of the Jewish population in the country and the sociocultural changes that are currently taking place in Arab society (Azaiza, in press;Ben-Ari & Azaiza, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This tendency may apparently exist also among new immigrants to Israel (Ben-Ari & Azaiza, 2003). Another possible explanation relates to the inclination of general practitioners to under diagnose an ED in minority groups in comparison to native-born individuals, (Becker, Franko, Speck, & Herzog, 2003) (it should be nonetheless noted that this study has been undertaken in the USA, and the findings might be different in Israel).…”
Section: Immigration To Israel and Eating Disordersmentioning
confidence: 90%
“…Whereas the Jewish-Israeli population, on the whole, lives according to social codes and norms of modern Western society, the Arab minority, regardless of belonging to any specific sub-group, maintain more traditional norms and social customs, particularly with respect to gender roles, marriage and divorce, family relationships and childrearing (Becker et al, 2003;Ben-Ari & Azaiza, 2003;Cnaan, 1987). Nevertheless many of them are connected to cable TV and radio, and may be potentially influenced to some extent by the Israeli western way of life (Eisenstadt, 1989).…”
Section: Eating Attitudes Among the Israeli Arab Populationmentioning
confidence: 99%